You are on page 1of 14

# Chapter 10

Standards
14.0 Students solve a quadratic equation by factoring or completing the
square.
19.0 Students know the quadratic formula and are familiar with its proof
by completing the square.
20.0 Students use the quadratic formula to find the roots of a second-
degree polynomial and to solve quadratic equations.
21.0 Students graph quadratic functions and know that their roots are the
x-intercepts.
23.0 Students apply quadratic equations to physical problems, such as the
motion of an object under the force of gravity.

Lesson 10.2
Lesson 10.2
Objectives:
1. Solve quadratic equations by quadratic formula.
2. Solve application problems using quadratic
equations.

Another technique for solving quadratic
equations is to use the quadratic formula.
The formula is derived from completing the
square of a general quadratic equation.
Derive the quadratic formula
from ax
2
+ bx + c = 0
where a≠ 0
Derive the quadratic formula from ax
2
+ bx + c = 0, a≠ 0
a
c
x
a
b
x
a
c
a
bx
x
a a
c
a
bx
a
ax
c bx ax
÷ =
|
.
|

\
|
- +
= + +
= + +
= + +
2
2
2
2
2
2
1
0
0
0
General form of a quadratic equation.
Divide all by a
Simplify
Subtract c/a on both sides.
Multiply by ½ and square the
result.
Derive the quadratic formula from ax
2
+ bx + c = 0, a≠ 0
2
2
2
2
2
2
2
2
2
2 2
2
4
4
2
4
4
4 2
4 2
2 2
a
ac b
a
b
x
a
a
a
c
a
b
a
b
x
a
c
a
b
a
b
x
a
b
a
c
a
b
x
a
b
x
÷
=
|
.
|

\
|
+
- ÷ =
|
.
|

\
|
+
÷ =
|
.
|

\
|
+
|
.
|

\
|
+ ÷ =
|
.
|

\
|
+ +
Add the result to both sides.
Simplify
Multiply by common denominator
Simplify
Derive the quadratic formula from ax
2
+ bx + c = 0, a≠ 0
a
ac b b
x
a
ac b
a
b
a
b
a
b
x
a
ac b
a
b
x
a
ac b
a
b
x
2
4
2
4
2 2 2
2
4
2
4
4
2
2
2
2
2
2
2
÷ ± ÷
=
÷
+ ÷ = ÷ +
÷
= +
÷
=
|
.
|

\
|
+
Square root both sides
Simplify
Common denominator/subtract
from both sides
Simplify
A quadratic equation written in
standard form, ax
2
+ bx + c = 0,
has the solutions.
a
ac b b
x
2
4
2
÷ ± ÷
=
Solve t
2
– 3t – 28 = 0
using the quadratic formula.
a = 1 b = -3 c = -28

4
2
8
2
11 3
7
2
14
2
11 3
2
11 3
2
121 3
÷ =
÷
=
÷
=
= =
+
=
±
=
±
=
x
x
x
x
2
112 9 3
) 1 ( 2
) 28 )( 1 ( 4 ) 3 ( ) 3 (
2
4
2
2
+ ±
=
÷ ÷ ÷ ± ÷ ÷
=
÷ ± ÷
=
x
x
a
ac b b
x
Solve 11n
2
– 9n = 1
using the quadratic formula.

=
÷ ÷ ÷ ±
=
) 11 ( 2
) 1 )( 11 ( 4 ) 9 ( 9
2
n =
+ ±
22
44 81 9
22
125 9 ±
22
5 5 9 ±
=
11n
2
– 9n – 1 = 0, so
a = 11, b = -9, c = -1
=
÷ ÷ ± ÷
=
) 1 ( 2
) 20 )( 1 ( 4 ) 8 ( 8
2
x
=
+ ± ÷
2
80 64 8
2
144 8± ÷
=
± ÷
=
2
12 8
20 4
or , 10 or 2
2 2
÷
÷
x
2
+ 8x – 20 = 0 (multiply both sides by 8)
a = 1, b = 8, c = ÷20
8
1
2
5
Solve x
2
+ x – = 0

using the quadratic formula.
Solve x(x + 6) = ÷30
using the quadratic formula.

=
÷ ± ÷
=
) 1 ( 2
) 30 )( 1 ( 4 ) 6 ( 6
2
x =
÷ ± ÷
2
120 36 6
2
84 6 ÷ ± ÷
So there is no real solution.
x
2
+ 6x + 30 = 0
a = 1, b = 6, c = 30
Solve 3y
4
= 6y
3
– 6y
2

using the quadratic formula.

=
÷ ÷ ±
=
) 1 ( 2
) 2 )( 1 ( 4 ) 2 ( 2
2
y =
÷ ±
2
8 4 2
2
4 2 ÷ ±
Hence, there are 3 solutions.
3y
4
– 6y
3
+ 6y
2
= 0
3y
2
(y
2
– 2y + 2) = 0
3y
2
= 0, y = 0 ; y
2
– 2y + 2 = 0
a = 1, b = -2, c = 2
i ± =1
Homework

Problem Set 10.2
TB pp. 613-616
(Multiples of 4 numbers 4, 8, …, 60)
62, 64, 66, 68